Elimination of Mortgage Rights on Property Rights Due to Land Acquisition for Public Interest at the Directorate of Land Procurement and Reservation Development - Burhanuddin, Mohamad (Jurnal Konstatering, 2024)
The purpose of this research is to find out how mortgage rights over property rights are removed due to land acquisition for public purposes at the Directorate of Land Procurement and Reservation Development, based on primary data and secondary data. This research uses a sociological juridical approach. The data that has been collected from library research is then analyzed qualitatively. The research data was analyzed using qualitative methods, in the research using the analytical knife of legal protection theory and the theory of the operation of the law. It is concluded that: 1. The abolition of ownership rights over land which is used as the object of collateral for mortgage rights because land acquisition is for public purposes, by law, will also automatically cause the mortgage rights to be extinguished. This means that the mortgage right can no longer be used as material collateral for a principal agreement that was made previously. Law Number 5 of 1960 has provided legal certainty regarding the abolition of ownership rights to land which can be caused by the land falling to the state and the land being destroyed. The state has the power to regulate and administer the allocation, use, supply and maintenance of land. 2. Removal of ownership rights to land for public purposes according to Law Number 5 of 1960 concerning Basic Agrarian Principles and other applicable laws and regulations can be carried out by paying attention to the provision of appropriate and fair compensation according to existing laws and regulations. Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest, Government Regulation Number 19 of 2021 concerning Implementation of Land Acquisition for Development in the Public Interest, Government Regulation No. 39 of 2023 concerning Amendments to Government Regulation Number 19 of 2021 concerning Implementation of Land Acquisition for Development in the Public Interest and its implementing provisions Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 19 of 2021 concerning Provisions for Implementing Government Regulation Number 19 of 2021 concerning Organizing Land Acquisition for Development in the Public Interest is the legal basis for carrying out the method of providing compensation to entitled parties.